2019
DOI: 10.1149/2.0132001jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Coupling k Convection-Diffusion and Laplace Equations in an Open-Source CFD Model for Tertiary Current Distribution Calculations

Abstract: A mathematical model to calculate tertiary current distributions in electrochemical reactors is presented taking into account the potential and concentration fields together with the hydrodynamics under laminar or turbulent conditions. Multiple reactions with different kinetic controls are considered at both electrodes. The computational algorithm solving the model was implemented in OpenFOAM. It allows the calculations for a given local potential at the working electrode, potentiostatic control, or for a fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…An interesting case of concentration and potential distributions occurs when the reactant interacts with the supporting electrolyte or it participates in homogeneous reactions in the solution bulk. This situation was analyzed by Hauser and Newman 42 considering four cases: (i) the deposition of gold in a KAuC1 4 -KC1 electrolyte, (ii) the reduction of copper and simultaneous generation of chloride ions from cuprous chloride in a supporting potassium chloride electrolyte, (iii) the deposition of zinc in alkaline solutions where the reduction of Zn(OH) 4 2− takes place, and (iv) the nitrate reduction in acidic nickel nitrate. Hsueh and Newman 43 considered the effect of bisulfate ions on copper deposition, and Van Den Bossche et al 44 reported the case of silver reduction from a nitrate-thiosulfate solution.…”
Section: Verification By Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An interesting case of concentration and potential distributions occurs when the reactant interacts with the supporting electrolyte or it participates in homogeneous reactions in the solution bulk. This situation was analyzed by Hauser and Newman 42 considering four cases: (i) the deposition of gold in a KAuC1 4 -KC1 electrolyte, (ii) the reduction of copper and simultaneous generation of chloride ions from cuprous chloride in a supporting potassium chloride electrolyte, (iii) the deposition of zinc in alkaline solutions where the reduction of Zn(OH) 4 2− takes place, and (iv) the nitrate reduction in acidic nickel nitrate. Hsueh and Newman 43 considered the effect of bisulfate ions on copper deposition, and Van Den Bossche et al 44 reported the case of silver reduction from a nitrate-thiosulfate solution.…”
Section: Verification By Comparison With Previous Studiesmentioning
confidence: 99%
“…Primary, secondary, and tertiary current distributions refer to diverse approximations that apply depending on the relative significance of fluid resistance, electrode kinetics, and mass-transfer. 2 Several cases, in increasing order of complexity, can be performed under the tertiary current distribution approach, i.e., (i) considering electrochemical reactions under mass-transfer control, 3 (ii) a combined mass-and charge-transfer kinetic control requiring the calculation of the potential distribution in the fluid phase, 4 and (iii) the same as the latter but including the migration term in the mass-transfer of each ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge of the hydrodynamic behavior is necessary in Equation () in order to calculate the concentration distribution of each species. For the most general case, the Navier–Stokes equations must be solved under laminar or turbulent flow conditions by means of CFD, which can be performed by using the open‐source software OpenFOAM as it was previously reported 42–44 …”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The usual boundary conditions to attend hydrodynamic calculations for a general case were outlined in our previous contributions 42,44 …”
Section: Mathematical Modelingmentioning
confidence: 99%